The Influence of Family Socioeconomic Status on Primary School Students’ Emotional Intelligence: The Mediating Effect of Parenting Styles and Regional Differences - Liu, Zixiao; Wu, Guohong (Frontiers in Psychology, 2022)
Select 180 primary school students from a city primary school in Shanghai, a developed area in eastern China, and 146 primary school students from a rural primary school in Jingzhou, a centrally underdeveloped area, as subjects. The method of scale is used to explore the influence of family socioeconomic status on the emotional intelligence of primary school students, and the mediating role of parenting styles in this influence and the difference in this effect in the two regions. The results show that: (1) The socioeconomic status and emotional intelligence of primary school students in Jingzhou are significantly lower than those of primary school students in Shanghai. In terms of parenting style, the emotional warmth and understanding of the fathers and mothers of Jingzhou’s primary school students are both significantly lower than those of Shanghai’s primary school students;(2) The socioeconomic status and emotional intelligence of the primary school students in Jingzhou were significantly and positively correlated with the parents' emotional warmth and understanding parenting styles, while the socioeconomic status and emotional intelligence of the primary school students in Shanghai were only significantly positively correlated with the father's emotional warmth and understanding parenting style;(3) Parenting style has a mediating effect between family socioeconomic status and emotional intelligence, but this effect has regional differences. The specific performance is as follows: the parents' emotional warmth and understanding parenting styles of the primary school students in Jingzhou play a partial mediating effect between the family socioeconomic status and emotional intelligence, while the Shanghai primary school students' fathers' emotional warmth and understanding parenting style plays a complete mediating effect in family socioeconomic status and emotional intelligence.